Engagement between patients with obesity and osteoarthritis and primary care physicians: a cross-sectional survey. Issue 8 (17th November 2021) - Horn, Deborah B.; Damsgaard, Christopher; Earles, Kathi; Mathew, Sheba; Nelson, Amanda E.
ABSTRACT: Purpose of the Study: Obesity is a major risk factor for development and worsening of osteoarthritis (OA). Managing obesity with effective weight loss strategies can improve patients' OA symptoms, functionality, and quality of life. However, little is known about the clinical journey of patients with both OA and obesity. This study aimed to map the medical journey of patients with OA and obesity by characterizing the roles of health care providers, influential factors, and how treatment decisions are made. Study Design: A cross-sectional study was completed with 304 patients diagnosed with OA and a body mass index (BMI) of ≥30 kg/m 2 and 101 primary care physicians (PCPs) treating patients who have OA and obesity. Results: Patients with OA and obesity self-manage their OA for an average of five years before seeking care from a healthcare provider, typically a PCP. Upon diagnosis, OA treatments were discussed; many (61%) patients reported also discussing weight/weight management. Despite most (74%) patients being at least somewhat interested in anti-obesity medication, few (13%) discussed this with their PCP. Few (12%) physicians think their patients are motivated to lose weight, but almost all (90%) patients have/are currently trying to lose weight. Another barrier to effective obesity management in patients with OA is the low utilization of clinical guidelines for OA and obesity management by PCPs. Conclusions: As the care coordinator of patients with OA and obesity, PCPs have a key role in supporting their patients in the treatment journey; obesity management guidelines can be valuable resources. PLAIN LANGUAGE SUMMARY: Osteoarthritis (OA) is a disease where the soft tissue between joints wears out causing pain and swelling. Obesity, having unhealthy extra body weight, increases the chances of a person getting OA and can make their OA worse. We wanted to learn more about what patients with OA and obesity experience as they try to manage their OA, including the doctors they talked to, the treatments they used, and if their weight was discussed. To better understand this journey, 304 people with OA and obesity and 101 primary care doctors who treat people with OA and obesity took an online survey. We found that people with OA and obesity tried to manage their OA symptoms on their own for an average of five years before going to a doctor for help. Many (54%) talked with their primary care doctor first. When people with obesity were told by doctors that they had OA, most people (61%) said that they talked about weight and weight loss. Most people (72%) also talked with their doctors about OA treatments. Few doctors (12%) thought their patients were serious about losing weight but almost all patients (90%) said they had tried or were still trying to lose weight. About half of doctors followed guidelines for taking care of people with OA (51%) and obesity (61%). Primary care doctors play a key role in helping patients with OA and obesity. Doctors can follow guidelines and provide treatment options including referrals to other specialists to support weight loss efforts. Graphical Abstract: uf0001